2021
DOI: 10.1039/d1bm00597a
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive analysis of pancreas organoids in synthetic hydrogels defines material-cell interactions and luminal composition

Abstract: The cultivation of cells forming three-dimensional structures like organoids holds great potential in different fields of life sciences and is gaining increasing interest with regards to clinical applications and personalised...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…To model necroptosis, adult stem cellderived primary human pancreatic organoids (hPOs) recapitulate the phenotype of the original pancreatic ductal epithelia and retain the pancreatic morphology and the distribution of ductal, acinar, mesenchymal and endothelial cells in a hollow spherical polarized cell monolayer enclosing a central lumen [79][80][81][82] . hPOs were maintained in matrix for 3 to 5 days to allow the formation of organoid spheres composed of a cellular monolayer surrounding a liquid-filled lumen, that expanded over time (Figures 6A and S6A), in line with previous findings 83 , after which necroptosis was induced. For this, matrix-embedded primary hPOs were incubated with BV6 (B) and the clinically-applicable pan-caspase inhibitor IDN-6556 (Emricasan; E), followed by time-lapse imaging and subsequent fluorescein diacetate (FDA)-and PI-based In conclusion, we identify LUBAC-mediated M1 poly-Ub as novel checkpoint that regulates necroptosis by controlling the cellular distribution of activated MLKL between membrane hotspot formation and endo-and exocytosis in cell lines of human origin and primary human organoids.…”
Section: Lubac-mediated M1 Poly-ub Regulates Necroptotic Cell Death I...supporting
confidence: 86%
“…To model necroptosis, adult stem cellderived primary human pancreatic organoids (hPOs) recapitulate the phenotype of the original pancreatic ductal epithelia and retain the pancreatic morphology and the distribution of ductal, acinar, mesenchymal and endothelial cells in a hollow spherical polarized cell monolayer enclosing a central lumen [79][80][81][82] . hPOs were maintained in matrix for 3 to 5 days to allow the formation of organoid spheres composed of a cellular monolayer surrounding a liquid-filled lumen, that expanded over time (Figures 6A and S6A), in line with previous findings 83 , after which necroptosis was induced. For this, matrix-embedded primary hPOs were incubated with BV6 (B) and the clinically-applicable pan-caspase inhibitor IDN-6556 (Emricasan; E), followed by time-lapse imaging and subsequent fluorescein diacetate (FDA)-and PI-based In conclusion, we identify LUBAC-mediated M1 poly-Ub as novel checkpoint that regulates necroptosis by controlling the cellular distribution of activated MLKL between membrane hotspot formation and endo-and exocytosis in cell lines of human origin and primary human organoids.…”
Section: Lubac-mediated M1 Poly-ub Regulates Necroptotic Cell Death I...supporting
confidence: 86%
“…Therefore, confocal Raman microscopy was implemented in this study as a nondestructive approach, which is already established for the analysis of cells in combination with biomaterials. [52][53][54] Multivariate data analysis of Raman stack scans acquired on the surface and inside the biofilm down to a depth of 10 mm revealed three different clusters, further assigned to the fiber network, the biomaterial consisting of bacteria and extracellular matrix and the background. The Raman spectrum of the fiber network was characterized by Raman signals of CA and gelatin (Fig.…”
Section: Biofilm Formation and Structurementioning
confidence: 99%
“…27 Jung et al reported a proof-ofconcept study to improve the throughput by collecting averaged signals from whole organoids and successfully studied over one hundred organoids under the same condition. 29 To facilitate pharmaceutical applications, improving the throughput of Raman measurements is required to examine spheroids under different treatment conditions 30,31 and assess the heterogeneity across spheroids. 8,32,33 Recently, Raman systems equipped with parallel excitation and signal acquisition have emerged to improve the throughput of Raman spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Raman spectroscopy emerged as a powerful analytical tool for studying living cells because it nondestructively assesses fingerprint-like features of vibrational information and requires minimal sample preparation. While Raman spectroscopy has been used to study 2D cellular models, including those of cell-drug interactions , and cellular changes during steatosis, , its low throughput limits its applications in examining spheroids, and only a few studies have been reported. Jamieson et al used Raman imaging to study the responses of tumor spheroids to anticancer drug therapy, demonstrating the potential of Raman spectroscopy in examining heterogeneities within and across spheroids . Jung et al reported a proof-of-concept study to improve the throughput by collecting averaged signals from whole organoids and successfully studied over one hundred organoids under the same condition …”
Section: Introductionmentioning
confidence: 99%